PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP PENDAPATAN PETANI WORTEL DI DESA SEMANGAT KECAMATAN MERDEKA KABUPATEN KARO - TONNY HENDRA NADEAK (LP2MTBM MAKARIOZ, 2021)
This study aims to determine the influence of socioeconomic factors (land area, number of dependents, education level andage) on the income of carrot farmers. The research was conducted in Semangat Village, Merdeka District, Karo Regency,North Sumatra Province. The determination of samples in this study using Simple Random Sampling method is as many as32 samples. The results showed that simultaneously the area of land (X1), the number of dependents (X2), the level ofeducation (X3) and the age of farmers (X4) had a significant effect on the income of carrot farming (Y) where obtained thevalue of F-count of 440,594 > F-table (2.73). Partially variable land area and education level positively and significantly affectthe income of carrot farming which can be seen from the value of t-count land area of 31.60 > t-table 1,697 and the value oft-count education level of 2,247 > t-table 1,697. While the variable number of dependents and age has a negative butinsignificant effect on the income of carrot farming.